Effects of Formation Pathways and Bromide Incorporation on Jarosite Dissolution Rates: Implications for Mars. Issue 6 (31st May 2022) - Zhou, Di‐Sheng; Yu, Xiao‐Wen; Chang, Rui; Zhao, Yu‐Yan Sara; Li, Xiongyao; Liu, Jianzhong; Lin, Honglei; Qi, Chao
Abstract: The dissolution rates of jarosite can constrain the duration of aqueous activities on Mars. To date, few studies have considered the influences of formation pathways and anion substitutions on jarosite dissolution rates. Here, we investigated how the formation pathways (Fe(II)‐oxidation and Fe(III)‐forced hydrolysis) and incorporation of bromide influence the dissolution rates of K‐jarosite under eight aqueous conditions combining T (277 K, 298 K, and 323 K) and αw (0.35, 0.75 and 1), except for 277 K−0.35αw . The results show that jarosite dissolution rates are primarily influenced by aqueous T ‐αw conditions. Formation pathways and Br contents are secondary factors and only become notable under low T (277 K) and low αw (0.35) conditions. Taking the jarosite formation pathways and Br incorporation into account, the maximum lifetime of jarosite may be slightly longer than that of the halogen‐free counterparts formed via Fe(III)‐forced hydrolysis. Jarosite of the Burns Formation (Meridiani Planum) and the Pahrump Hills member (Gale Crater) are likely formed via Fe(II)‐oxidation and halogen‐bearing. Their estimated field lifetime (∼150 μm–1 mm particles) in low‐ T groundwater may last for hundreds of thousand years to a few million years. Jarosite in the Vera Rubin Ridge would share a similar lifespan if low‐ T solutions account for jarosite formation and subsequent interactions; otherwise, interactions with hydrothermal fluids (∼100°C) would substantially shorten the jarosite lifetime. We conclude that Martian jarosite may survive continuous aqueous interactions for up to a few million years, indicating an extended duration of aqueous environments than previously thought. Plain Language Summary: Since prolonged exposure to fluids would effectively dissolve jarosite, the presence of jarosite in the Martian sedimentary rocks indicates relatively short aqueous environments in ancient Mars. Previous studies on jarosite dissolution rates have mainly focused on environmental conditions. However, the influences of jarosite formation pathways and anion substitutions in jarosite are less explored. We investigated the dissolution rates of K‐jarosite formed via two pathways, Fe(II)‐oxidation under ambient T and Fe(III) in hydrothermal solutions. Jarosite bearing different halogen contents was examined for aqueous conditions varying T (277 K, 298 K, and 323 K) and salinity (highly saline brines to pure water). When taking formation pathways and Br incorporation of jarosite samples into account, jarosite may survive continuous aqueous interactions for up to a few million years, which is longer than the previous estimation. Jarosite can therefore indicate an extended duration of aqueous environments on the Martian surface than previously thought. Key Points: Formation pathways and bromide substitutions influence jarosite dissolution rates, but to a lesser extent than aqueous conditions When considering formation pathways and halogen incorporation, the maximum lifetime of jarosite may be longer than previously thought The newly estimated lifetime of jarosite lasts for a few million years, allowing an extended duration of aqueous environments on Mars